Controllability of Neutral Impulsive Stochastic Integrodifferential Equations Driven by a Rosenblatt Process and Unbounded Delay - Ramkumar, K.; Ravikumar, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this manuscript, we establish the controllability of neutral impulsive stochastic integrodifferential equations driven by a Rosenblatt process with infinite delay in separable Hilbert space. The controllability results is obtained by using fixed-point technique and via resolvent operator.